Current E-Business Initiatives And Usage And Its Impact On E-Business Readiness In Telekom Malaysia (An Exploratory Study Of Employee Perception) - A Wahid, Tajuddin (2000)
This exploratory study covers the key areas of concern influencing current e-business initiatives and usage within Telekom Malaysia and how they have has impacted the e-business readiness. The findings of this survey on current e-business initiatives and usage and its impact on TM's e-business readiness are based on more than 280 survey responses supplied by executive employees of TM located throught Malaysia.